Do tangível ao intangível: dinâmica entre valores, materialidade e restauração de documentos cartográficos - Ana Cristina Torres Campos (2023)
The present work examines the attribution of values as an essential element in decision-making within the field of graphic documents and paper conservation. Through the examination of case studies, we sought to identify the main values considered by conservators at the moment of decision-making, in a reverse process to the traditional method of significance assessment. To carry out this research, 27 case studies were collected regarding treatments executed on three typologies of cartographic documents: maps, celestial and terrestrial globes, and architectural plans and drawings. These typologies were selected because it is believed that they possess a set of characteristics that satisfactorily emulate the entire field of paper objects and graphic documents. Each case study was individually analyzed, based on the typology of values and assessment of significance method published by Fredheim and Khalaf (2016). The associative aspects of cartographic documents were found to be the basis for all practices carried out on these items, but it is the functional, evidentiary, and associative aspects that directly influence treatment decisions made by conservators and restorers dealing with them. This dynamic justifies the field’s traditional focus on the materiality of objects and points to a need to holistically understand this class of objects, because preservation, conservation, and restoration practices are situated within the confluence between the intangible and tangible dimensions of objects.